2011
DOI: 10.1007/s11199-011-9981-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Young Women Expect Gender Equality in Their Future Lives? An Answer From a Possible Selves Experiment

Abstract: This study examined young women's expectations about gender equality in their future careers and marriages. The study implemented a possible selves method in which 114 undergraduate women from a Midwestern university in the United States were randomly assigned to envision themselves as married mothers employed either full-time, part-time, or not at all and possessing either an advanced degree or a bachelor's degree. Participants indicated their expectations for gender equality by estimating their own and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
3
31
0
3
Order By: Relevance
“…These findings are similar to those reported by other researchers who have found that there is a nonegalitarian norm in romantic relationships where men have more power and privilege than women, although some movement toward egalitarianism can be observed (Gerson, 2009;Sassler & Miller, 2011;Sprecher & Felmlee, 1997). Our findings are also consistent with findings from studies examining emerging adults' imagined futures, where women participants have reported a mixture of realism and optimism regarding egalitarianism in their future couple relationships (Fetterolf & Eagly, 2011;Orrange, 2003). Although young women are aware of existing general inequalities between men and women, they are optimistic about their capabilities of being able to achieve more egalitarian arrangements than the previous generation (Fetterolf & Eagly, 2011).…”
Section: Following and Resisting Gendered Rules For Anger And Women'ssupporting
confidence: 92%
“…These findings are similar to those reported by other researchers who have found that there is a nonegalitarian norm in romantic relationships where men have more power and privilege than women, although some movement toward egalitarianism can be observed (Gerson, 2009;Sassler & Miller, 2011;Sprecher & Felmlee, 1997). Our findings are also consistent with findings from studies examining emerging adults' imagined futures, where women participants have reported a mixture of realism and optimism regarding egalitarianism in their future couple relationships (Fetterolf & Eagly, 2011;Orrange, 2003). Although young women are aware of existing general inequalities between men and women, they are optimistic about their capabilities of being able to achieve more egalitarian arrangements than the previous generation (Fetterolf & Eagly, 2011).…”
Section: Following and Resisting Gendered Rules For Anger And Women'ssupporting
confidence: 92%
“…Accordingly, women's status in the workplace has improved in multiple ways: The gender pay gap has narrowed (Mandel & Semyonov, ), the significance of employer discrimination in promotions has declined (Meyersson Milgrom & Petersen, ), increasing numbers of mothers remain employed (Bureau of Labor Statistics, ; Percheski, ), and so forth. In contrast, gender equality in the family has lagged behind: Women still do most of the caretaking and housework (Sayer, ) and stereotypically gendered patterns in romantic relationships pervade (Fetterolf & Eagly, ; Hamilton, Geist, & Powell, ). Where there has been improvement for women in the family realm, it results more from increased time living apart (marriage delay and divorce) and a reduction in women's total amount of time spent on housework rather than from a convergence in gendered behavior (England, ; Sayer, ).…”
mentioning
confidence: 99%
“…Los resultados de este estudio también concuerdan con otras investigaciones (Bianchi et al, 2000;Davis & Greenstein, 2004;Fetterolf & Eagly, 2011) que han demostrado que cuanto mayor es el nivel educativo de la persona, sus actitudes serán más equitativas que aquellos que tienen un menor nivel. Por tanto, la importancia de la educación en la formación de la igualdad sugieren varias vías para una intervención continuada y pertinente en la Educación Superior, lo cual implica, en primer lugar, mejorar el acceso y la participación de los jóvenes a la educación, y en segundo lugar, incorporar el género de manera transversal tanto en la educación reglada como en la formación universitaria.…”
Section: Discussionunclassified